AZAS KESEIMBANGAN TERHADAP PRAKTEK PERJANJIAN SEWA BELI PADA LEMBAGA PEMBIAYAAN (FINANCE) - Rosyidi Hamzah; Sridevi Ayunda (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2022)
The practice of leasing is mostly carried out by financial institutions in running their business. The lease purchase stands on the agreement that has been agreed by the parties. The debtor is required to pay installments in the form of rent to the creditor and if lease-purchase installments have been fulfilled in accordance with agreement, the object of the lease-purchase is automatically purchased by the debtor. If the debtor defaults in paying the rent installments, the creditor can withdraw the object of the lease anytime and anywhere because the object of the lease still belongs to the creditor. The problem that occurs in the lease purchase agreement is that when the debtor defaults and the object of the lease is withdrawn by the creditor, the debtor no longer has the right to the rental installments that he has paid so far, so the expectations of the debtor to have the object is lost and the rent installments are also lost. The equality in the purchase agreement must be applied in the lease purchase agreement. The legal vacuum in the practice of leasing must be filled by creating new laws in the field of leasing. Keywords: Purchase, Legal Vacuum, Equality